Colleges and schools-College of Arts and Humanities-Music-0110 (1987)
Members of the president's Quintet at California State University, Fresno are (left to right) Sandy Heinrichs of Reedly, Dayahna Rogers of Sanger, Dean Olmstead of Fresno, Joel Everett II of Vacaville and Richard Martinez of Fresno.